Karakteristik Kimia dan Organoleptik Selai Oles Kenari (Canarium indicum L.) Dengan Penambahan Susu Full Cream - Hitijahubessy, Maria S; Mailoa, Meitycorfrida; Moniharapon, Erynola (Universitas Pattimura, 2021)
The purpose of the study was to determine the effect of adding the best of full cream milk on the chemical and organoleptic characteristics of canarium nuts spread. A completely randomized design with the addition of full cream milk concentration consisted of 5 treatment levels, namely 0%, 3%, 6%, 9%, and 12%. The result showed that adding 9% full cream milk to walnut jam was the best treatment with overall acceptable chemical and organoleptic characteristics.